Odnos in stališča zdravstvenih delavcev do darovanja organov po smrti ter donorske in transplantacijske dejavnosti v Sloveniji - Uštar, Barbara (Teorija in praksa, 2024)
Not only are healthcare workers key to performing medical procedures in the organ donation and transplantation system, but their attitudes to deceased organ donation can strongly influence people’s willingness to donate, which is a precondition for organ transplantation. This article presents the results of a qualitative analysis of in-depth interviews with healthcare workers directly involved in organ donation and transplantation. It shows the diversity of attitudes held by healthcare workers regarding this specific field of medicine, with the main findings highlighting the specificities and potential vulnerabilities of the Slovenian system. There is potential for the formalised inclusion of different health profiles in the country’s donor and transplant system, and for questioning the organ donation consent system and the educational gaps concerning donor medicine.
Keywords: attitudes; darovanje organov po smrti; deceased organ donation; donor medicine; donorska medicina; healthcare workers; odnos do darovanja organov; organ transplantation; presaditev organov; Presaditev organov, tkiv itd.; transplant medicine; transplantacijska medicina; Zdravnik in bolnik; zdravstveni delaci; zdravstveni delavci